Comic transformations in Shakespeare - Nevo, Ruth (Routledge, 2013)
First published in 1980. In this study of Shakespeare's ten early comedies, from The Comedy of Errors to Twelfth Night, the concept of a dynamic of comic form is developed; the Falstaff plays are seen as a watershed, and the emergence of new comic protagonists - the resourceful, anti-romantic romantic heroine and the Fool - as the summit of the achievement. The plays are explored from three complementary perspectives - theoretical, developmental and interpretative which lead to a further understanding of the powerful relation between the plays' formal compl.